2021
DOI: 10.1177/03057356211045114
|View full text |Cite
|
Sign up to set email alerts
|

Popular music lyrics and the COVID-19 pandemic

Abstract: A limited amount of previous research suggests that deteriorating socioeconomic conditions may be associated with greater popularity of music lyrics featuring negative emotional content and references to relationships. The present research considered this in charting popular music before and during the first 6 months of the COVID-19 pandemic. A dataset based on the song lyrics of the top-5 charting weekly songs in the United Kingdom and the United States from January 1999 to August 2020 was computer-analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…Similarly, threatening circumstances in the United States between 1955 and 2003 (as evidenced by fluctuations in US unemployment rates and other economic indicators) were associated with a preference for songs that were longer, slower, dealt with meaningful issues, and were more comforting and romantic (Pettijohn & Sacco, 2009b). Putter et al (2022) also found that, from 1999-2020, a monthly measure of economic misery in the US was positively associated with the presence of negatively valenced lyrics in charting songs. Influxes in negatively valenced lyrics might reflect contrahedonic emotion regulation (increasing unpleasant emotions or decreasing pleasant emotions), which can be both useful (e.g., when used for reflection or introspection, or to garner feelings of connectedness) or harmful (e.g., when maintaining or increasing negative emotions leading to distress or impairments; Parrott, 2014).…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…Similarly, threatening circumstances in the United States between 1955 and 2003 (as evidenced by fluctuations in US unemployment rates and other economic indicators) were associated with a preference for songs that were longer, slower, dealt with meaningful issues, and were more comforting and romantic (Pettijohn & Sacco, 2009b). Putter et al (2022) also found that, from 1999-2020, a monthly measure of economic misery in the US was positively associated with the presence of negatively valenced lyrics in charting songs. Influxes in negatively valenced lyrics might reflect contrahedonic emotion regulation (increasing unpleasant emotions or decreasing pleasant emotions), which can be both useful (e.g., when used for reflection or introspection, or to garner feelings of connectedness) or harmful (e.g., when maintaining or increasing negative emotions leading to distress or impairments; Parrott, 2014).…”
mentioning
confidence: 85%
“…The potentially contradictory predictions arising from two theoretical approaches previously discussed, absence of direct prior evidence, and idiosyncratic nature of the COVID pandemic, meant that we opted to approach the quantitative analyses as an exploratory study guided by the following two research questions: RQ2: How does the lyrical content of the pandemic playlist differ from charting popular music during the COVID-19 pandemic with respect to (a) interpersonal relationships and (b) valence? Putter et al (2022) found that charting songs during the start of the pandemic reflected greater social isolation and lower positive affect relative to pre-pandemic data, so it is possible that the pandemic playlist might differ from that within the chart data.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…A number of other recent studies have attempted to predict the sales chart performance of songs based on various structural and acoustic features of the music (e.g., Askin & Mauskapf, 2017;Herremans et al, 2014;Interiano et al, 2018;Ren & Kauffman, 2017;Zangerle et al, 2020) and lyrics (Dhanaraj & Logan, 2005;Putter et al, 2021;Raza & Nanath, 2020). However, two other studies of music popularity have considered variables similar to processing fluency.…”
mentioning
confidence: 99%